ACUTE TOXICITY STUDIES OF METHANOLIC BARK EXTRACT OF FICUS RACEMOSAAND ROOT EXTRACT OF CISSAMPELOS PAREIRA - CHOUDHURY PRADEEP KUMAR; JADHAV SACHIN (International Journal of Pharma and Bio Sciences, 2013)
The acute toxicity study of Ficus racemosa and Cissampelos pareira, was investigated. The acute toxicity test of the extracts was determined according to the OECD guidelines No. 420 (Organization for Economic Co-operation and Development). Female Wistar rats (150–180 g) were used for this study. A starting dose of 2000 mg/kg (P.O.) of the test samples were given to various extract groups containing 5 rats in each group. Rats were randomly selected for the study and tail marked to provide individual identifications. Rats were observed immediately after dosing during first 30 minutes, periodically during the first 24 hours, with special attention given during first 4 hours, and daily thereafter for 14 days (OECD guidelines, 2001). During the first four hours rats were tested for following various responses like behavioral response,neurological response and autonomic response and were accessed by their respective parameters.All the animals were found healthy and the extracts were found to be safe up to a dose of 2000 mg/kg.